Memorable messages and the evaluation of relational transgressions. Issue 4 (8th August 2018) - Miczo, Nathan; Flood, Michelle; Fitzgerald, Josh
ABSTRACT: A memorable messages framework was used to examine evaluations of relational transgressions. One hundred and fifty-eight participants described a relational transgression, and then provided a memorable message pertaining to the transgression. Sixty-four participants provided a memorable message relevant to their transgression. Six categories of memorable messages emerged, with personal responsibility, acceptance, and treatment of self and others being the most common. Factor analysis revealed three dimensions used to evaluate those messages (evaluation, catharsis, rehearsal). The rehearsal dimension was negatively correlated with transgression severity and hurtfulness, and positively associated with the decision to confront the partner. Results offer some support for the control theory explanation. Additionally, a category of "remembered messages" allowed exploration of a distinct kind of hurtful message.